GaP/GaNP Heterojunctions for Efficient Solar‐Driven Water Oxidation. Issue 21 (31st March 2017) - Kargar, Alireza; Sukrittanon, Supanee; Zhou, Chang; Ro, Yun Goo; Pan, Xiaoqing; Dayeh, Shadi A.; Tu, Charles W.; Jin, Sungho
Abstract : The growth and characterization of an n‐GaP/i‐GaNP/p + ‐GaP thin film heterojunction synthesized using a gas‐source molecular beam epitaxy (MBE) method, and its application for efficient solar‐driven water oxidation is reported. The TiO2 /Ni passivated n‐GaP/i‐GaNP/p + ‐GaP thin film heterojunction provides much higher photoanodic performance in 1m KOH solution than the TiO2 /Ni‐coated n‐GaP substrate, leading to much lower onset potential and much higher photocurrent. There is a significant photoanodic potential shift of 764 mV at a photocurrent of 0.34 mA cm −2, leading to an onset potential of ≈0.4 V versus reversible hydrogen electrode (RHE) at 0.34 mA cm −2 for the heterojunction. The photocurrent at the water oxidation potential (1.23 V vs RHE) is 1.46 and 7.26 mA cm −2 for the coated n‐GaP and n‐GaP/i‐GaNP/p + ‐GaP photoanodes, respectively. The passivated heterojunction offers a maximum applied bias photon‐to‐current efficiency (ABPE) of 1.9% while the ABPE of the coated n‐GaP sample is almost zero. Furthermore, the coated n‐GaP/i‐GaNP/p + ‐GaP heterojunction photoanode provides a broad absorption spectrum up to ≈620 nm with incident photon‐to‐current efficiencies (IPCEs) of over 40% from ≈400 to ≈560 nm. The high low‐bias performance and broad absorption of the wide‐bandgap GaP/GaNP heterojunctions render them as a promising photoanode material for tandem photoelectrochemical (PEC) cells to carry out overall solar water splitting. Abstract : An n‐GaP/i‐GaNP/p + ‐GaP thin film heterojunction is synthesized for efficient solar‐driven water oxidation. The TiO2 /Ni‐coated n‐GaP/i‐GaNP/p + ‐GaP photoanode provides high performance in 1m KOH solution with an onset potential of ≈0.4 V versus reversible hydrogen electrode (RHE), a photocurrent of 7.26 mA cm −2 at 1.23 V versus RHE, and a broad absorption spectrum up to ≈620 nm.